Modelling the Origins of Nationally-Bound Administrative Heritages: A Historical Institutional Analysis of French and British Firms - Calori, Roland; Lubatkin, Michael; Very, Philippe; Veiga, John F. (Organization Science, 1997)
Various determinants have been proposed to explain the persistence of nationally-bound administrative heritages. In this paper, we propose an overall model that integrates these contingent determinants. Our model is based on historical analysis, a method of theory building that first conceptualizes a model and then utilizes it as an exploratory lens for viewing historical evidence. The originality of our model comes from the theory-based bias that we introduce into the model as a way to avoid the trap of multi-causalism. Specifically, we select a nation's educational system as our model's leading determinant, for educational institutions and particularly schools more than other institutions both shape a nation's beliefs about “how things ought to be done,” and transmit those beliefs and practices to successive generations. We draw the theoretical grounding for this bias using a theory of socialization which posits that the schemas that individuals internalize during their early formative stages of development greatly influence the way that they will later construct reality. We found our model to be useful in clarifying the underlying historical reasons why British and French firms rely on different integrative mechanisms when establishing headquarters-subsidiary linkages. Indeed, by analyzing the history of these two nations and the routines and rationalities imposed by their respective set of institutions in the context of our model, we find an overall mosaic, or gestalt, that is fully consistent with their present-day administrative practices. For example, we find that French managers today tend to heavily rely on centralized controls and headquarters intervention because of the influences of a number of key historical elements. These include the way their ancestors dealt with threats of invasion and ethnic diversity; the leadership styles of past French monarchies and elected officials; the manner in which the French colonies were controlled and the French school system organized; and the way the French government responded to economic problems that came from being a late participant in the two industrial revolutions. These also include the philosophies of the revered seventeenth-century French thinkers; the family structures that have existed in France since the middle ages; and the enduring influence of the Catholic ethos. Similarly, we use our model to present a different, yet equally compelling, mosaic image to explain why British managers have tended to rely on an administrative heritage, based on decentralization, “laissezfaire” and autonomy. Finally, and perhaps most important, we show that the explanation we arrived at using this inductive method of theory building is fully consistent with the empirical conclusions we derived using contemporary methods of organization science. In so doing, we demonstrate that these two approaches, when combined, can inform and enrich theory building and thereby lead to a more thorough understanding of organizational phenomena such as administrative heritage.